حرف الجرّ اللام وأثر التّفسير في خروجه عن معناه - يونس يونس; حسين خديجة (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
يتناول البحث حرف الجرّ اللام وأثر التّفسير في خروجه عن معناه، فعلماء اللغة منذ البداية كانوا فقهاء وقضاة، يهتمّون بدراسة النّصّ القرآني لاستخراج الأحكام الشّرعيّة منه . يبدأ البحث بمقدّمة، ثمّ يعرض لصلة الدّراسات الفقهيّة وعلم التّفسير بالنّحو ، بعد ذلك يذكر معاني حرف الجرّ اللام كما وردت في أمّهات كتب النّحو ، ثمّ يتناول بعض الآيات القرآنيّة التي ورد فيها حرف الجرّ اللام ، ويذكر شرح المفسّرين لآيات القرآن الكريم ، وكيفيّة تخريج دلالة اللام إلى معانٍ مختلفة ، لتناسب السّياق القرآني ، ويذكر البحث المعاني الإضافيّة التي رأى المفسّرون أنّ اللام الجارّة تكون عليها ، وينتهي البحث بخاتمة تشتمل على أهمّ نتائج البحث . This research dealt with the (lam) preposition and the impact of explanation in making it out of its meaning, from the beginning the linguistics were judges and jurists who studied the Quran texts and read out the legality rules. The research began with an introduction, and showed the link of jurisprudential studies and explanation with grammar, then it mentioned the meanings of the (lam) preposition as it had been contained in grammar books, after that, it dealt with some Quran verses where the (lam) preposition were written, and it mentioned how explainers addressed the verses of the Quran, where had come the imperative lam, and how their meanings had fit the Quranic context, and it contained the additional meanings which explainers felt that the (lam) preposition should be, and it ended with the conclusion which included the most important results of the research.